A SimpleProbe® real‐time PCR assay for differentiating the canine parvovirus type 2 genotype. Issue 1 (31st August 2018) - Hoang, Minh; Wu, Hung‐Yi; Lien, Ying‐Xiu; Chiou, Ming‐Tang; Lin, Chao‐Nan
Abstract : Background: Canine parvovirus type 2 (CPV‐2) causes an important canine viral disease worldwide. CPV‐2 belongs to the Protoparvovirus genus in the family Parvoviridae. An amino acid change at position 426 of the VP2 protein differentiate types of CPV‐2, designated as CPV‐2a (Asn), CPV‐2b (Asp), and CPV‐2c (Glu). In this study, we compared CPV‐2 genotyping results obtained by SimpleProbe ® real‐time PCR and DNA sequencing analysis to identify the accuracy and sensitivity of these methods. Methods: One hundred rectal swabs were collected from CPV‐2 naturally infected dogs from 2015 to 2017 at the Animal Disease Diagnostic Center, National Pingtung University of Science and Technology. CPV‐2 genotyping was performed by SimpleProbe ® real‐time PCR and DNA sequencing to compare results. Results: CPV‐2a (n = 23), 2b (n = 6) and 2c (n = 71) genotyping results obtained by both techniques were identical with specificity of 100% for SimpleProbe ® assay. In the SimpleProbe ® assay, amplifying the DNAs prepared from the clinical specimens showed three distinct melting curve peaks. CPV‐2b had the highest melting peak of 57.8°C (CI 95%: 57.7‐58.5°C) followed by CPV‐2c with a slightly lower melting peak of 52.3°C (CI 95%: 52.2‐53.2°C) and CPV‐2a with the lowest peak of 50.2°C (CI 95%: 50.1‐50.5°C). Conclusion: This study developed a novel method for genotyping CPV‐2 strains using the SimpleProbe ® real‐time PCR assay. This assay is a reliable and sensitive tool for differentiating between the CPV‐2a, 2b and 2c and this technique can be used for molecular CPV‐2 epidemiology studies.